The development of creative tourism in Ukraine and globally during the COVID-19 pandemic - Liubarets, Vladyslava; Zinkova, Iryna; Zemlina , Yuliia; Voroshylova, Hanna; Tymeichuk, Anna (Turyzm/Tourism, 2022)
The article identifies the challenges to the creative industries in tourism as an important phenomenon in the conditions of the urgent global issue of COVID-19. The concepts of “creative industries”, “creative tourism”, and signs of creative tourism (economic, social and ecological sustainability) have been specified. An analysis has been made, and the issues and opportunities for introducing creative industries into tourism have been determined. It is emphasized that creative tourism, as a self-sufficient product, easily changes format and subject matter depending on the objectives set, while remaining creative in its nature and purpose. The main opportunities for the development of tourist services and creative tourism priority areas have been outlined. Recommendations for introducing creative technologies by relevant government institutions and tourism enterprises have been suggested.